Heterogeneity in dog red blood cells: sodium and potassium transport (The Rockefeller University Press, 1979)
After incubation in isotonic KCl, dog red blood cells can be separated by centrifugation into subgroups which assume different cell volumes and possess different transport characteristics. Those red cells which swell in isotonic KCl exhibit a higher permeability to K and possess a greater volume dependence for transport of K than those red cells which shrink. A high Na permeability characterizes cells which shrink in isotonic KCl and these cells exhibit a larger volume-dependent Na flux than those red cells which swell. These two subgroups of red cells do not seem to represent two cell populations of different age. The results indicate that the population of normal cells is evidently heterogeneous in that the volume-dependent changes in Na and K permeability are distributed between differnt cell types rather than representing a single cell type which reciprocally changes its selectivity to Na and K.